If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + -1x = -497 Solving 3 + -1x = -497 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1x = -497 + -3 Combine like terms: 3 + -3 = 0 0 + -1x = -497 + -3 -1x = -497 + -3 Combine like terms: -497 + -3 = -500 -1x = -500 Divide each side by '-1'. x = 500 Simplifying x = 500
| -2(x+1)+1=20 | | 1x+4=9 | | 24=7x+-4(2x+-4) | | -0.16=3.7 | | -0.13x=3.9 | | 2(x+3)+5x=15-(2x+18) | | 60-4x=4x^2 | | y^2-3y-5=0 | | 4x+36=108 | | 9y+5=5*(y+5) | | 3x^2+49x=0 | | -14=-4[9x-1] | | 9(7-2-3-(9-8))=0 | | 0.5x+17+x=20 | | 2x+7+x=-143x | | 2x+7+x=-14 | | 9x(7-2-3-(9-8))=0 | | 7a+11=73 | | 6x+11=x+16 | | 4(a)(b)-3(a)(b^2)= | | -2[a+6]=-22 | | 3-3y=5 | | -4x+12-3x=-6 | | 21x^2+xy-10y^2=0 | | 7x=x-42 | | 7x+3+6x+7=180 | | 0=(8x-5)(2x-3) | | y=30x+72 | | 20=9k+2 | | -213=-5x+3(7x+-7) | | 7x^2y-(-11(x^2)y)= | | 5(-2-5m)=17+2m |